PENGARUH MEDIA PEMBELAJARAN ARTICULATE STORYLINE PADA MATERI KERAGAMAN BUDAYA TERHADAP MINAT BELAJAR SISWA KELAS V SDN SINDANGHEULA 02 - Uus Agustina; Elan Elan (Universitas Negeri Medan, 2021)
Abstrac : The Influence of Articualte Storyline Learning Media on Cultural Diversity Materials on the Learning Interests of Class V SDN Sindangheula 02. This study aims to determine the effectiveness of Articulate Storyline learning media on Civics subjects, especially on cultural diversity material for class V SDN Sindangheula 02. This study uses quantitative research methods. using The One Group Pretest Posttest research design. The samples taken were 14 students using the Saturated Sampling technique. From the results of research analysis, it shows that there is an effect of using Articulate Storyline learning media. The average value of the experimental class has increased from 70 to 90.Keywoards: Articulate Storyline, cultural diversity, student interest in learning.Abstrak : Pengaruh Media Pembelajaran Articualte Storyline Pada Materi Keragaman Budaya Terhadap Minat Belajar Siswa Kelas V SDN Sindangheula 02. Penelitian ini bertujuan untuk mengetahui keefektifan media pembelajaran Articulate Storyline pada mata pelajaran PKn khususnya pada materi keragaman budaya kelas V SDN Sindangheula 02. Penelitian ini menggunakan metode penelitian kuantitatif menggunakan desain penelitian The One Group Pretest Posttest. Sampel yang diambil adalah 14 siswa dengan menggunakan teknik Sampling Jenuh. Dari hasil analisis penelitian, menunjukkan adanya pengaruh penggunaan media pembelajaran Articulate Storyline. Nilai rata-rata kelas eksperimen mengalami peningkatan dari 70 menjadi 90.Kata Kunci : Articulate Storyline, keragaman budaya, minat belajar siswa.